Deaf Genetic Testing and Psychological Well‐Being in Deaf Adults. Issue 4 (21st February 2013) - Palmer, Christina G. S.; Boudreault, Patrick; Baldwin, Erin E.; Fox, Michelle; Deignan, Joshua L.; Kobayashi, Yoko; Sininger, Yvonne; Grody, Wayne; Sinsheimer, Janet S.
Abstract: Limited data suggest that enhanced self‐knowledge from genetic information related to non‐medical traits can have a positive impact on psychological well‐being. Deaf individuals undertake genetic testing for deaf genes to increase self‐knowledge. Because deafness is considered a non‐medical trait by many individuals, we hypothesized that deaf individuals receiving a genetic explanation for why they are deaf will experience increased psychological well‐being. We report results from a prospective, longitudinal study to determine the impact of genetic testing ( GJB2, Cx26; GJB6, Cx30) on perceived personal control (PPC), anxiety, and depression in deaf adults ( N  = 209) assessed following pre‐test genetic counseling as well as 1‐month and 6‐months following test result disclosure. Participants were classified as Cx positive ( n  = 82) or Cx negative/inconclusive ( n  = 127). There was significant evidence for Cx group differences in PPC and anxiety over time (PPC: Cx group*time interaction p  = 0.0007; anxiety: Cx group*time interaction p  = 0.002), where PPC scores were significantly higher, and anxiety scores were significantly lower for the Cx positive group relative to the negative/inconclusive group following test result disclosure. Compared to pre‐test, PPC scores increased at 1‐month ( p  = 0.07) and anxiety scores decreased at 6‐months ( p  = 0.03) for the Cx positive group. In contrast, PPC scores decreased ( p  = 0.009, p  < 0.0001) and anxiety scores increased ( p  = 0.09, p  = 0.02) for the Cx negative/inconclusive group at 1‐ and 6‐months post test result disclosure. Genetic testing for deaf genes affects the psychological well‐being of deaf individuals. Increasing deaf adults' access to genetic testing may potentially enhance self‐knowledge and increase psychological well‐being for those who receive a genetic explanation, which could offer downstream health benefits.